PREPARATION OF XYLOSE AND KRAFT PULP FROM POPLAR BASED ON FORMIC/ACETIC ACID /WATER SYSTEM HYDROLYSIS - Junping Zhuang; Lu Lin; Jing Liu; Xiaolin Luo; Chunsheng Pang; Pingkai Ouyang (BioResources, 2009)
A formic/acetic acid/water system was used in the ratios of 30:60:10, 20:60:20, and 30:50:20 separately for efficient hydrolysis and bioconversion of poplar chips, under the solid/liquid ratio of 1:12(g/ml), at 105 oC for 30, 45, 60, 75, and 90 min, respectively. The highest yield of 69.89% was at a formic/acetic acid /water ratio of 30:50:20(v/v/v), with solid/liquid in the ratio of 1:12(g/ml) at 105 oC for 90min. Lower kappa number and similar yield were achieved when hydrolytic residual woodchips were used for kraft pulping with over 2% Na2O and temperature 5 °C lower compared to untreated chips. Pulps from prehydrolysis-treated chips were easy to beat. But the tensile index, tear index, and burst index of the handsheets obtained from pulp with lowest kappa number from prehydrolysis-treated poplar chips were lower than those of the pulp from the untreated chips. Considerable xylose could be obtained from the prehydrolysis stage following kraft pulping under the same conditions for prehydrolysis-treated chips and untreated chips. However, by building on the mature kraft pulping and xylitol processes, large amounts of xylose from the hemicellulose were obtained in prehydrolysis, allowing production of high-valued products via biorefinery pathways. An economical balance of chemical dosage, energy consumption, pulp properties, and xylose value for prehydrolysis with organic acid should be reached with further investigation.